THE USE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN IMPROVING THE QUALITY OF PHYSICAL EDUCATION LESSONS - Umarov Abdusamat Abdumalikovich; Umarova Zulxumor Urinboyevna; Alisherova Moxira Axrorjon kizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article reflects the role and advantages of using innovative pedagogical technologies in the organization and conduct of physical education classes, sports competitions, wellness and sports events in higher educational institutions, the specificity of the interactive method.